E-commerce contracts for sale of goods and consumer protection - Sheela Jayabala; Rahmah Ismail (Penerbit Universiti Kebangsaan Malaysia, 2014)
This book confronts the abstract confront law principles in the light of modern contract law approach. The facilitative function of contract law is seen in the light of social realism which demands contractual justice, i.e fairness